The regulation of DNA end resection by chromatin response to DNA double strand breaks - Chen, Bo-Ruei; Sleckman, Barry P. (Frontiers in Cell and Developmental Biology, 2022)
DNA double-strand breaks (DSBs) constantly arise upon exposure to genotoxic agents and during physiological processes. The timely repair of DSBs is important for not only the completion of the cellular functions involving DSBs as intermediates, but also the maintenance of genome stability. There are two major pathways dedicated to DSB repair: homologous recombination (HR) and non-homologous end joining (NHEJ). The decision of deploying HR or NHEJ to repair DSBs largely depends on the structures of broken DNA ends. DNA ends resected to generate extensive single-strand DNA (ssDNA) overhangs are repaired by HR, while those remaining blunt or minimally processed can be repaired by NHEJ. As the generation and repair of DSB occurs within the context of chromatin, the resection of broken DNA ends is also profoundly affected by the state of chromatin flanking DSBs. Here we review how DNA end resection can be regulated by histone modifications, chromatin remodeling, and the presence of ssDNA structure through altering the accessibility to chromatin and the activity of pro- and anti-resection proteins.